Manpower Development Activities - DESIDOC, Director (DESIDOC Journal of Library & Information Technology, 2002)
The R&D and other S&T departments in general require information specialists who are abreast of current information technologies for providing adequate information support. The need for such information support is all the more important for DRDO where the technological expertise expected is very high. DESIDOC conducts training and user-education programmes on various important aspects of information science and technology. These programmes are designed to provide adequate knowledge and skill to the officers and staff working in the libraries technical information centres of DRDO labs/estts. http://dx.doi.org/10.14429/dbit.11.2.3030